2019
DOI: 10.3390/su11154115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Payment Delays at Two Links in Payment Chains on the Progress of Construction Projects: System Dynamic Modeling and Simulation

Abstract: Payment is the lifeblood of construction projects. However, steady fund flow is rare in construction projects. This paper focused on a quantitative evaluation of the impact of payment delays at the two links (i.e., from owner to general contractor and from general contractor to subcontractor) on the progress of a construction project. A hybrid research method combining the interpretative structural modeling (ISM) method and system dynamics was used to simulate the complex relationships between a payment delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Hou et al [28] proposed a model to explore the behavior of project cash flow system and profitability under different payment problems and conditions. Another study by Xie et al [29] modeled the impacts of delayed payment on the progress of construction projects and concluded that shortening the payment period for contractors and subcontractors will accelerate the flow of funds and ensure smooth progress. Furthermore, Dabirian et al [6] presented a model to analyze the effects of financial policies related to owners, financial institutions, labor, and suppliers on contractors' cash flow.…”
Section: Cash Flow Management In Construction Projectsmentioning
confidence: 99%
“…Hou et al [28] proposed a model to explore the behavior of project cash flow system and profitability under different payment problems and conditions. Another study by Xie et al [29] modeled the impacts of delayed payment on the progress of construction projects and concluded that shortening the payment period for contractors and subcontractors will accelerate the flow of funds and ensure smooth progress. Furthermore, Dabirian et al [6] presented a model to analyze the effects of financial policies related to owners, financial institutions, labor, and suppliers on contractors' cash flow.…”
Section: Cash Flow Management In Construction Projectsmentioning
confidence: 99%
“…Cui et al (2010) applied SD to evaluate the effect of some cash policies and project operation on the project cash flow. Xie et al (2019) employed SD to evaluate the effects of payment delays on construction projects progress, especially cash flow. The simulation results of the study indicated that shortening the payment period as a powerful policy will accelerate the flow of funds and smoothen the project progress.…”
Section: Introductionmentioning
confidence: 99%
“…(2010) applied SD to evaluate the effect of some cash policies and project operation on the project cash flow. Xie et al. (2019) employed SD to evaluate the effects of payment delays on construction projects progress, especially cash flow.…”
Section: Introductionmentioning
confidence: 99%